The honourable company : - John, Keay (Macmillan Publishing Co ; Toronto : Maxwell Macmillan Canada, 1991)
The english east india company was the greatest trading power of all times, and the most famous-and infamous-of the companies established by the great european powers. The company's offices stretched from the streets of London to as far away as china, australia, india, and the american colonies. For more than two centuries the company dominated trade, raised armies, demolished nations, and established one of the most far-flung empires the world has ever known. Without it there would have been no british empire...